Beneficiary characteristics and vaccinations in the end-stage renal disease Medicare beneficiary population, an analysis of claims data 2006–2015. Issue 52 (19th December 2017) - Shen, Angela K.; Kelman, Jeffrey A.; Warnock, Rob; Zhang, Weiwei; Brereton, Stephaeno; McKean, Stephen; Wernecke, Michael; Chu, Steve; Gellin, Bruce G.
Abstract: Background: The Advisory Committee on Immunization Practices (ACIP) routinely recommends three vaccines – influenza, hepatitis B, and pneumococcal vaccines – for End-Stage Renal Disease (ESRD) dialysis patients. Methods: We sought to assess vaccination coverage among fee-for-service (FFS) Medicare beneficiaries with ESRD who received Part B dialysis services at any point from January 1, 2006 through December 31, 2015 (through June 30, 2016 for influenza). To assess influenza vaccination rates in a given influenza season, we restricted the population to beneficiaries who were continuously enrolled in Medicare Parts A and B throughout all twelve months of that season. To assess hepatitis B and pneumococcal vaccine coverage following dialysis initiation, we developed a Kaplan-Meier curve for all patients who began dialysis between 2006 and 2015. Results: For influenza vaccination, we identified an average of approximately 325, 000 ESRD dialysis beneficiaries enrolled through each influenza season from 2006–2015. Seasonal influenza vaccination rates steadily increased during the 10-year period, from 52% in 2006–2007 to 71% in 2015–2016. The greatest increases in influenza vaccination appear in non-white beneficiaries with overall utilization in non-whites higher than in whites (p < .001). For the hepatitis B and pneumococcal vaccinations, we identified over 350, 000 ESRD dialysis beneficiaries who began dialysis over the 10-year study window. The probability of receiving a hepatitis B vaccine within the first three years of entering into the ESRD program was higher (77%) than the probability of receiving any pneumococcal vaccine (53%). 45% of ESRD patients completed at least one dose of the two hepatitis B series (three-dose or four-dose) at any time during the study period. Conclusions: Opportunities exist at regional and facility levels to improve vaccination coverage. Compliance to ACIP recommendations may directly affect risk for ESRD dialysis patients for complications from diseases that can be mitigated by vaccination.